Raman Scattering Spectra and Dielectric Relaxation Behavior of Pzt-Pzn-Pmnn Ceramics - Vuong, Le Dai; Gio, Phan Dinh; Kieu, Vo Thi Thanh (International Journal of Chemistry and Materials Research, 2014)
The 0.8Pb(Zr0.48Ti0.52)O3–0.125Pb(Zn1/3Nb2/3)O3–0.075Pb(Mn1/3Nb2/3)O3 + 0.7 wt% Li2CO3 + 0.3 wt% Fe2O3ceramics (PZT-PZN-PMnN) have been prepared by two-stage calcination method. The inﬂuences of sintering temperature on dielectric properties and Raman scattering in the PZT-PZN-PMnN relaxor ferroelectric ceramics have been investigated in detail. The dielectric studies showed that the degree of diffuseness (γ) increased with the increase of the sintering temperatures from 900 to 1000 °C, indicating that the dielectric relaxation behavior was increased; while at higher sintering temperature above 1000 °C, the γ decreased. The dielectric measurement results are in good agreement with the Raman scattering spectra analysis of the samples. It was found that the value of full wide of half maximum (FWHM) of silent B1+E mode reached the maximum value at the sintering temperature of 1000 oC, which showed similar trends to γ. At sintering temperature of 1000 oC, the highest dielectric constant (max) of 23600 and the γ value of 1.84.